Lifetime risk of developing impaired glucose metabolism and eventual progression from prediabetes to type 2 diabetes: a prospective cohort study - Ligthart, Symen; van Herpt, Thijs T W; Leening, Maarten J G; Kavousi, Maryam; Hofman, Albert; Stricker, Bruno H C; van Hoek, Mandy; Sijbrands, Eric J G; Franco, Oscar H; Dehghan, Abbas (The lancet. Diabetes & endocrinology, 2016)
Data are scarce for the lifetime risk of developing impaired glucose metabolism, including prediabetes, as are data for the risk of eventual progression from prediabetes to diabetes and for initiation of insulin treatment in previously untreated patients with diabetes. We aimed to calculate the lifetime risk of the full range of glucose impairments, from normoglycaemia to prediabetes, type 2 diabetes, and eventual insulin use. In this prospective population-based cohort analysis, we used data from the population-based Rotterdam Study. We identified diagnostic events by use of general practitioners' records, hospital discharge letters, pharmacy dispensing data, and serum fasting glucose measurements taken at the study centre (Rotterdam, Netherlands) visits. Normoglycaemia, prediabetes, and diabetes were defined on the basis of WHO criteria for fasting glucose (normoglycaemia: ≤6·0 mmol/L; prediabetes: >6·0 mmol/L and <7·0 mmol/L; and diabetes ≥7·0 mmol/L or use of glucose-lowering drug). We calculated lifetime risk using a modified version of survival analysis adjusted for the competing risk of death. We also estimated the lifetime risk of progression from prediabetes to overt diabetes and from diabetes free of insulin treatment to insulin use. Additionally, we calculated years lived with healthy glucose metabolism. We used data from 10 050 participants from the Rotterdam Study. During a follow-up of up to 14·7 years (between April 1, 1997, and Jan 1, 2012), 1148 participants developed prediabetes, 828 developed diabetes, and 237 started insulin treatment. At age 45 years, the remaining lifetime risk was 48·7% (95% CI 46·2-51·3) for prediabetes, 31·3% (29·3-33·3) for diabetes, and 9·1% (7·8-10·3) for insulin use. In individuals aged 45 years, the lifetime risk to progress from prediabetes to diabetes was 74·0% (95% CI 67·6-80·5), and 49·1% (38·2-60·0) of the individuals with overt diabetes at this age started insulin treatment. The lifetime risks attenuated with advancing age, but increased with increasing BMI and waist circumference. On average, individuals with severe obesity lived 10 fewer years without glucose impairment compared with normal-weight individuals. Impaired glucose metabolism is a substantial burden on population health, and our findings emphasise the need for more effective prevention strategies, which should be implemented as soon in a person's life as possible. The substantial lifetime risk of prediabetes and diabetes in lean individuals also supports risk factor control in non-obese individuals. Erasmus MC and Erasmus University Rotterdam; Netherlands Organisation for Scientific Research; Netherlands Organisation for Health Research and Development; Research Institute for Diseases in the Elderly; Netherlands Genomics Initiative; Netherlands Ministry of Education, Culture and Science; Netherlands Ministry of Health, Welfare and Sports; European Commission; and Municipality of Rotterdam.